Analisis Perputaran Piutang dan Perputaran Persediaan dalam Mengukur Kinerja Keuangan pada Perum Bulog - Sulawati Sulawati; Andi FItri Sugi Angka (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study was to determine receivables turnover and inventory turnover in measuring financial performance at Perum Bulog Sub Divisi Regional Parepare in accordance with industry standards. Data collection techniques used are observation, interviews, documentation and literature study, the analytical method used in this research is quantitative and qualitative data. By using the ratio analysis of accounts receivable turnover, inventory turnover. The object of research is to use financial statements from 2019-2021 in the form of balance sheets and profit and loss, the results of calculating accounts receivable turnover, inventory turnover and average days of inventory at Perum Bulog Sub-Division Regional Parepare for the 2019-2021 period show that this value is still below the industry standard average while the calculation of the average days of receivables collection is in accordance with the average industry average. Receivable turnover in 2019 (14 times), 2020 (12 times) and 2021 (15 times) is not good because it is below the industry average standard of ≥ 15 times in the 2019-2021 period. The average days for collection of accounts receivable in 2019 (26 days), 2020 (24 days) and 2021 (24 days) are good because they comply with the industry average standard of ≤ 60 days. Inventory turnover in 2019 (1 time), 2020 (1 time) and 2021 (2 times) is not good because it is below the industry average standard, which is ≥ 20 times. The average inventory days in 2019 (365 days), 2020 (365 days) and 2021 (183 days) were not good because they exceeded the industry standard limit of ≤ 19 days. It can be seen that the accounts receivable turnover and inventory turnover in measuring financial performance are not in accordance with industry standards.